Analysis of Variables that Affect Tax Avoidance in Banking Sector Companies in Southeast Asia - Iqbal Bagus Prakosa; Gunasti Hudiwinarsih (STIE Perbanas Surabaya, 2018)
Tax is one of the largest revenues the state has and it is compulsory for both citizens and companies to pay to the state. The collected funds are used by the state to build state infrastructure and others. However, not all individuals or companies are willing to pay tax voluntarily. Some taxpayers even carry out tax avoidance. There are many factors that may affect tax avoidance practices, such as institutional ownership, gender diversity on board of directors, audit committee, and fi rm size. This study aims to determine the effect of institutional ownership, gender diversity on board of directors, audit committee and fi rm size on tax avoidance by using current effective tax rate approach and SPSS test tool version 22. The sample consists of 568 banking sector companies in Southeast Asia and they are listed on Orbis that publish fi nancial statements in English, gain profi t, and pay taxes in the research period. Based on the research results, it is found that institutional ownership has a signifi cant effect on tax avoidance. Likewise, audit committee and fi rm size also have a signifi cant effect on tax avoidance. However, gender diversity on board of directors has no signifi cant effect on tax avoidance.